Aerodynamic analysis on unsteady characteristics of a ducted fan hovering in ceiling effect. Issue 1 (31st December 2023) - Luo, Yiwei; Ai, Tianfu; He, Yuhang; Zhao, Zhiran; Xu, Bin; Qian, Yuping; Peng, Jie; Zhang, Yangjun
Abstract : Ducted fans have been widely used in unmanned aerial vehicles (UAVs) for various operations due to the high efficiency, low noise and high safety. Proximity effects caused by the confined environment, including the ceiling effect (CE), bring significant interference to the aerodynamic performance of ducted fans, which serves as a main challenge to stability. In this study, the computational fluid dynamic simulation with the sliding mesh technique and the Unsteady Reynolds Averaged Navier-Stokes (URANS) method is conducted to evaluate the ceiling effect. Time-averaged simulation results show that the ceiling effect results in the increase of both rotor thrust and duct thrust. Transient simulation results show that there is a critical distance of 0.4 rotor radius. The ceiling effect leads to little fluctuation in thrust for distances greater than 0.4 rotor radius, but substantial unsteadiness in the flow field for distances less than 0.4 rotor radius. The unsteady movement of vortex structures results in thrust fluctuations with frequencies typically lower than the blade passing frequency of 200 Hz. The fluctuation accounts for up to 40% of the total thrust. The results are essential to the flight controller design and UAV path planning for enhancement of flight stability in ceiling effect.